Functional characterization of the developmental genes asm2, asm3, and spt3 required for fruiting body formation in the filamentous ascomycete Sordaria macrospora. Issue 2 (8th July 2021) - Lütkenhaus, Ramona; Breuer, Jan; Nowrousian, Minou
Abstract: The formation of fruiting bodies is one of the most complex developmental processes in filamentous ascomycetes. It requires the development of sexual structures that give rise to meiosporangia (asci) and meiotic spores (ascospores) as well as surrounding structures for protection and dispersal of the spores. Previous studies have shown that these developmental processes are accompanied by significant changes of the transcriptome, and comparative transcriptomics of different fungi as well as the analysis of transcriptome changes in developmental mutants have aided in the identification of differentially regulated genes that are themselves involved in regulating fruiting body development. In previous analyses, we used transcriptomics to identify the genes asm2 and spt3, which result in developmental phenotypes when deleted in Sordaria macrospora . In this study, we identified another gene, asm3, required for fruiting body formation, and performed transcriptomics analyses of Δasm2, Δasm3, and Δspt3. Deletion of spt3, which encodes a subunit of the SAGA complex, results in a block at an early stage of development and drastic changes in the transcriptome. Deletion mutants of asm2 and asm3 are able to form fruiting bodies, but have defects in ascospore maturation. Transcriptomics analysis of fruiting bodies revealed a large overlap in differentially regulated genes in Δasm2 and Δasm3 compared to the wild type. Analysis of nuclear distribution during ascus development showed that both mutants undergo meiosis and postmeiotic divisions, suggesting that the transcriptomic and morphological changes might be related to defects in the morphogenesis of structural features of the developing asci and ascospores.